Assessing Fiscal Sustainability : A Cross-Country Comparison - Croce, Enzo (IMF Working Papers; Working Paper ;, 2003)
To monitor fiscal sustainability, this paper proposes a recursive algorithm derived from the law of motion of the debt-to-GDP ratio, subject to a government reaction function that links convergence to the targeted debt ratio with primary fiscal surpluses. Based on quarterly estimates of this algorithm in the 1990s, 12 developed and developing countries are ranked according to their degree of sustainability. For a number of countries, the paper finds evidence of causality between the fiscal policy stance and growth-adjusted real interest rates.